Ecosystem services in urban and regional planning instruments - Deppisch, Sonja; Heitmann, Anne; Savaşçı, Günden; Lezuo, Dagmar (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
Land-use in complex urban regions and their future development is uncertain, especially in view of (global) change conditions and the planetary boundaries discussed. An encompassing discussion and weighting within planning is necessary, on what ecosystems offer which kind of services to urban and regional societies and how this current supply and further potentials can be sustainably used. This is essential to contribute to a resilient urban and regional development. Scientific discussions on the role of ecosystem services in spatial planning do partly investigate the current status-quo of references to ecosystem services. This paper presents results from two German case study regions on the extent of references to ecosystem services in existing spatial planning instruments. Both binding as well as non-binding regional and urban development concepts were considered. Although none of the planning instruments explicitly uses the term “ecosystem services”, references to ecosystem services can be identified in all instruments. However, the majority of classified ecosystem services is not linked to specific objectives. This evokes questions on if spatial planning is oriented on keeping options open to act in the future and what the detected blind spots tell about the interpretation of the vision of sustainable spatial development.
Keywords: ecosystem services; urban region; regional plan; regulatory land-use plan; urban development concept; regional development concept; resilience; sustainable land-use